THE IMPACT OF WORKPLACE DISCIPLINE ON EMPLOYEE PERFORMANCE AT PT. PHARMA HEALTH CARE - Ade Risna Sari; Darmawati Manda; Karyono Karyono; Syamsu Rijal; Maskur Maskur (Pusat Riset dan Inovasi Nasional, 2023)
The purpose of this study is to investigate and analyses how employee performance is impacted by workplace rules, rewards, and job characteristics. PT. Pharma HealthCare was the site of this study. In this study, there were 501 employees in the population and 92 participants in the sample. The method of sampling employs a non-probability sampling strategy. Utilizing a questionnaire gathering method to gather data from primary sources. The IBM SPSS 25 programmer was the analytical instrument employed. The findings demonstrated that, in contrast to incentives, which had no influence on employee performance, work discipline and job features had a considerable beneficial impact on employee performance.